Varistor in the Inverator Circuit Starting Energy Saver to Reduce Water Pump Electric Current - Faisal Irsan Pasaribu; Noorly Evalina; Partaonan Harahap (Budapest International Research in Exact Sciences (BirEx) Journal, 2021)
In general, the water pump is often used automatically, according to the use of the water faucet when it is opened. This automatic water pump system often triggers a surge in electric current when the water pump is on or off. This surge in electric current will increase compared to the nominal electric current. With increased current capacity, sometimes we face problems with the quality of electrical power in the electrical system, and will also increase electricity bills. The purpose of this research is to improve the quality of power to save electricity, reduce electric current when the water pump is used, so as to reduce the cost of using electricity bills, especially for water pumps. The use of Varistors in the Inverator Starting Energy Saver circuit is very influential in protecting the load when there is a surge in current even though it is momentary or long, so that it can improve the quality of electrical power at the water pump load. The data is carried out on measuring current, voltage, cos phi and frequency when the water pump is used without using an inverator. After making these measurements the measurement data can be saved as a comparison for the measurement data, which uses the installation of an inverator starting energy saver which is connected in parallel with the power source and also connected to the water pump. By installing the inverter starting energy saver circuit to improve the quality of electric power. The use of a varistor in the inverator starting Energy saver circuit clearly produces a current of 1.274 A and the voltage is 216 V without using an inverator. Furthermore, when using the inverter circuit, it produces a current of 1.098 A and the voltage drops by 207.6 V. The decrease in the working voltage of the water pump is still within the standard 5%.